Efficiency of industrial enterprise management in the context of future digital transformation - Khimich, Sv. (Management and Entrepreneurship: Trends of Development, 2024)
The purpose of the article is to investigate the issue of efficiency of industrial enterprise management in the context of digital transformation.The author has completed research on the efficiency of industrial enterprise management in the context of digital transformation. It has been found that changes occurring in the business environment require enterprises of a systematic and harmonious approach to digital transformation for successful adaptation and implementation of the necessary changes.The characterization of forms of management of an industrial enterprise, depending on the structure of management of the enterprise, is considered. The advantages and disadvantages of enterprise management structures such as linear, functional, linear-functional, software-target structure, matrix, divisional. For each of the management structures of the industrial enterprise, the author describes the possibilities for digital transformation of the industrial enterprise.  It is noted that an important aspect is the effective implementation of transformation stages, which allows enterprises not only to adapt to modern requirements, but also to become successful in a fast -variable digital environment. The implementation of all stages of digital transformation determines the key areas of implementation of digital processes in the enterprise, creating a foundation for sustainable development and competitiveness.The theoretical and methodological base of the study is based on the study of scientific works of leading scientists in the field of entrepreneurship, as well as on their own interpretation of the efficiency of management of an industrial enterprise, taking into account the possibilities of digital transformation of the enterprise.The study used methods such as analysis and synthesis, methods of historical and logical modeling. Theoretical approaches were also applied, including formalization method, the method of "from abstract to specific", as well as the method of economic interpretation. From a practical point of view, further scientific research in this area has the potential to reveal the optimal strategies for integration of digital technologies in enterprises. This can help not only solving modern challenges, but also expanding opportunities for sustainable development and enhancing competitiveness.JEL Classification: L60; L69